PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN TERHADAP KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Survei Pada SKPD se-Kabupaten Bintan ) - Putra, Firmansyah Dwi; Anugrah, Rita; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of human resource capacity, utilization of information technology and internal accounting control on the reliability of district financial government report of Bintan District. The data in this study used the primary data obtained from distributing questionnaires to head and accounting/ financial administration staff of Bintan district which amounted to 60 institution. This study used multiple regression analysis method using SPSS version 20 The results of this study indicate that human resource capacity, utilization of information technology, and internal accounting control have a positive effect on the reliability of local government financial reporting in Bintan Regency. With significance value for human resource capacity variable is 0,000, variable utilization of information technology equal to 0,014 and internal accounting control variable 0.000.Keywords :Reliability, Human Resource Capacity, Utilization of Information Technology and Internal Accounting Control System